2016
DOI: 10.1021/acsmedchemlett.6b00369
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxypyridine-N-oxide-Embedded Aurones as Potent Human Tyrosinase Inhibitors

Abstract: With the aim to develop effective and selective human tyrosinase inhibitors, we investigated aurone derivatives whose B-ring was replaced by a non-oxidizable 2-hydroxypyridine-N-oxide (HOPNO) moiety. These aurones were synthesized and evaluated as inhibitors of purified human tyrosinase. Excellent inhibition activity was revealed and rationalized by theoretical calculations. The aurone backbone was especially found to play a crucial role, as the HOPNO moiety alone provided very modest activity on human tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 43 publications
3
54
0
1
Order By: Relevance
“…At present, though a wide range of tyrosinase inhibitors from natural and synthetic sources have been reported, only a few of them, in addition to being effective, are known as safe compounds. No significant advances concerning toxicity issues of tyrosinase inhibitors seem to emerge from the literature survey carried out for this review, the relevant papers just reporting the results of in vitro cytotoxicity experiments [49,52,75,81,95,126,129,[131][132][133]136,137,147,163,[176][177][178]184,185,192,198,202,203,207,210,212,214,215,239,240,242,245] and only a few of in vivo experiments on zebrafish [130,206,209]. Therefore, it is essential to examine the efficacy and safety of inhibitors by checking e.g., whether or not the candidate inhibitor is substrate of tyrosinase being modified on exposure to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, though a wide range of tyrosinase inhibitors from natural and synthetic sources have been reported, only a few of them, in addition to being effective, are known as safe compounds. No significant advances concerning toxicity issues of tyrosinase inhibitors seem to emerge from the literature survey carried out for this review, the relevant papers just reporting the results of in vitro cytotoxicity experiments [49,52,75,81,95,126,129,[131][132][133]136,137,147,163,[176][177][178]184,185,192,198,202,203,207,210,212,214,215,239,240,242,245] and only a few of in vivo experiments on zebrafish [130,206,209]. Therefore, it is essential to examine the efficacy and safety of inhibitors by checking e.g., whether or not the candidate inhibitor is substrate of tyrosinase being modified on exposure to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies used B16 murine melanoma cell lines as a model [52,55,75,85,95,96,99,114,122,123,[127][128][129][132][133][134][135]138,139,151,153,155,163,, although some papers using zebrafish as an in vivo whole animal model have also been published [55,116,206]. As to the human sources, data on inhibition of human recombinant or purified tyrosinase [9,207], human melanoma cells [130,136], normal human melanocytes [208][209][210][211], or human skin models consisting of reconstructed three-dimensional human epidermis [212][213][214][215] have been published (Figure 21). The results of clinical trials have also been reported for well recognized skin depigmenting agents [216,217] such as thiamidol, that, as stated also above, is one of the most striking examples of a pigmentation inhibitor exhibiting significant higher activity on human than on mushroom tyrosinase [9,218...…”
Section: Human and Animal Tyrosinase Phenolic Inhibitorsmentioning
confidence: 99%
“…An abundant literature is dedicated to mushroom tyrosinase inhibitors for human applications but unfortunately, currently used inhibitors lack the affinity and selectivity required for human tyrosinase targeting applications. Moreover, harmful toxicity has often been reported (Haudecoeur et al, 2016). Therefore, there is an urgent need for novel selective human tyrosinase inhibitors that match efficacy and safety standards required for the development of products aimed to human use.…”
Section: Human Tyrosinase Inhibitorsmentioning
confidence: 99%
“…Aurones (2-benzylidenebenzofuran-3(2H)-ones), naturally occurring flavonoids act as inhibitors of melanin biosynthesis in human melanocytes. It also act as effectors of mushroom tyrosinase and as molecular probes for the investigation of the binding-site structural homology between mushroom and bacterial tyrosinase (Haudecoeur et al, 2016). On the other hand, HOPNO, a catechol-mimicking, nonoxidizable moiety, is a potent inhibitor of mushroom tyosinase (Ki = 1.8 μM).…”
Section: Human Tyrosinase Inhibitorsmentioning
confidence: 99%
“…Recently, increasing attention has been focused on aurones because both natural aurones and synthetic analogs exhibited excellent antitumor , antioxidant , antibacterial, and anti‐inflammatory activities, as well as acted as potent multifunctional defense agents against Alzheimer's disease . In addition, aurones have been proved to be valuable inhibitors of human tyrosinase to prevent hyperpigmentation‐related abnormality . These studies indicate that aurone has evolved to be an excellent leading scaffold for the development of various analogs with significant biological activity.…”
Section: Introductionmentioning
confidence: 99%